The Influence of Brand Trust, Customer Relationship Management (CRM) and Customer Satisfaction on Starbucks Coffee Customer Loyalty at Taman Hive Cawang, East Jakarta - Diana Legilorina; Resti Hardini; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine Brand trust, Customer Relationship Management (CRM) and Consumer Satisfaction with Customer Loyalty Starbucks Coffee TamansariHive Cawang East Jakarta. This researcher uses multiple linear regression data analysis techniques and uses the SPSS program version 23. The results of this study show the influence of Brand Trust on customer loyaticity. This is shown through the t-count T test of 7,205 > 1,660 tables and significant (0.757 < 0.05) (X1). Costomer Relationship Management also has a positive and significant influence on customer loyalty. This is shown through the t-count T test of 4,004>1,660table and is significant of (0.279<0.05) (X2). Consumer satisfaction also has a positive and significant influence on customer loyalty. This is shown through the t-count T test 0.447>1.660table and significant (0.656<0.50) (X3).